Researching and writing a dissertation : an essential guide for business students - Fisher, C. M. (Colin M.); Buglear, John. (Harlow, England ; New York : Financial Times/Prentice Hall, 2010)
This textbook contains sections on how to choose a topic and design the project, how to write a critical literature review, concepts, conceptual frameworks and theories, collecting and analysing research material, interpreting the research material and, finally, framing arguments and writing the dissertation.
Choosing a topic and designing the project -- Writing a critical literature review -- Concepts, conceptual frameworks and theories -- Collecting and analysing research material -- Interpreting the research material -- Framing arguments and writing up -- Using software for research.
Includes bibliographical references and index.
Keywords: Dissertations, Academic; Business -- Research; Report writing